SPORTS PROGRAMS ON IRAQI CHANNELS AND THEIR INFLUENCE ON YOUTH - Eskander, Mahmoud Muazaz (PT. Antis International Publisher, 2026)
Objective: This study examines the impact of sports programs on Iraqi youth, focusing on how these programs affect social, psychological and behavioral values, and aims to evaluate the role of sports programs in shaping positive and negative behaviors among young viewers. Method: This study is based on the descriptive and analytical method, where a random sample of 300 Iraqi youth between the ages of 18 and 30 years from all regions was selected, and data were collected by using a questionnaire to find out how many people watch sports programs, how good these programs are, and how they affect values like discipline, cooperation, and love for sports. Result: The results showed that sports programs have a significant positive impact on social values such as discipline and teamwork, as the results showed that viewing hours contribute to enhancing these values significantly, while the impact of programs on negative behaviors such as sports fanaticism was small, and statistical analyses, such as the Chi-square test and regression analysis, also showed that there is a strong relationship between watching sports programs and enhancing positive behaviors. Novelty: The study confirms that sports programs play an important role in promoting social and psychological values among Iraqi youth, with the need to work on reducing the negative effects related to sports fanaticism by improving the content of these programs.